The Effect of Kisspeptin-10 on Cisplatin-Induced Testicular Oxidative Stress - Arkalı, Gözde; Acısu, Tutku Can; Ekmen, Edanur Güler; Kızıl, Meltem; Özgür, Fatma Beril; Çay, Mehmet; Aksakal, Mesut (My University, 2025)
Objective: Cisplatin, one of the anticarcinogenic drugs, causes damage to spermatogenic cells, sertoli cells and leydig cells. This study aimed to investigate the kisspeptin-10 effect against oxidative stress caused by cisplatin in male reproductive organs and its negative effects on spermatological parameters. Materials and Methods: In the experiment, 34 male Sprague Dawley rats were used. Rats were divided into 4 groups as control, cisplatin, kisspeptin-10 and cisplatin+kisspeptin-10. Cisplatin 5 mg/kg/single dose and kisspeptin-10 50 nmol/kg dose were administered intraperitoneally for 7 days. Results: In the cisplatin group, testicular malondialdehyde level increased (p<0.001), catalase enzyme activity (p<0.001) and glutathione level (p<0.01) decreased, sperm motility (p<0.05) and testicular (p<0.01) and seminal vesicle (p<0.001) weights decreased. In the cisplatin group administered kisspeptin-10, it was determined that testicular malondialdehyde level decreased (p<0.001), glutathione level increased (p<0.01), sperm motility increased (p<0.05), and testicular (p<0.01) and seminal vesicle (p<0.001) weights increased compared to the cisplatin group. Conclusion: As a result, it was revealed that Kisspeptin-10 showed improving effects on spermatological parameters by reducing oxidative stress that is effective in cisplatin-induced testicular damage.
Keywords: Oxidative Stress; Cisplatin; Testes; Kisspeptin-10